Effects of high-intensity functional training on physical fitness and sport-specific performance among the athletes: a systematic review with meta-analysis - Wang, Xinzhi; Soh, Kim Geok; Samsudin, Shamsulariffin; Deng, Nuannuan; Liu, Xutao; Zhao, Yue; Akbar, Saddam (Public Library of Science, 2023)
Objective This study aims to meta-analyze the impact of high-intensity functional training on athletes’ physical fitness and sport-specific performance.